YIELD OF PLEURAL FLUID COLLECTED FOR CULTURE IN TYPICAL/SPECIALIZED BLOOD CULTURE BOTTLES VS COLLECTED IN ORDINARY SYRINGES/BOTTLES (The Research of Medical Science Review, 2025)
Background: Pleural infections are highly morbid and lethal. Microbiologic diagnosis is critical in guiding proper antimicrobial therapy, but conventional pleural fluid culture on sterile bottles is of low sensitivity. New evidence suggests that inoculation of pleural fluid into blood culture bottles (BCBs) enhances diagnostic yield. Objective: To compare the microbiological yield of pleural fluid cultures collected in blood culture bottles versus standard sterile containers and assess their diagnostic performance. Methods: In the present prospective study at Pak Emirates Military Hospital Rawalpindi, 120 adult patients of suspected pleural infections were enrolled. Pleural fluid samples from each patient were inoculated in both aerobic/anaerobic BCBs and regular sterile containers simultaneously. All the samples were processed in accordance with microbiology laboratory protocols. The primary outcomes were culture positivity rate, distribution of pathogens, contamination rate, and time to positivity. Statistical analysis was done through Chi-square test and Kaplan-Meier analysis, and the level of p < 0.05 was taken as significant. Results: Positive cultures from BCBs were obtained from 53.3% of 120 patients compared with 28.3% from standard containers (p < 0.001). Anaerobes were obtained only from the BCBs. The time to positivity was significantly reduced when using BCBs (18.6 hours vs 36.4 hours). Contamination rates were very low and comparable using both procedures. The most frequently isolated pathogens were Streptococcus pneumoniae, Staphylococcus aureus, and Escherichia coli. Conclusion: Blood culture bottles significantly improve the microbiological yield of pleural fluid cultures, reduce time to detection, and improve recovery and identification of anaerobes that are not recovered by standard conventional methods. In practice, routine application of BCBs should be considered in clinics, and guidelines for standardized pleural fluid collection are needed.